Freiburg personality inventory in inflammatory bowel disease: diagnosis and psychotherapeutic needs - Rada, Cornelia; Țieranu, Cristian George; Gheonea, Dan Ionuț; Ionescu, Elena Mirela (Anales de Psicología / Annals of Psychology, 2024)
Despite recent discoveries, patients with inflammatory bowel disease (IBD) still face challenges with attainment of remission. The objectives of the study were to identify the characteristics of patients with the Freiburg Personality Inventory and the intensity of the intestinal disease, comorbidities that could be related to the personality of the subjects. Data were collected in the period 2019–2020 from 46 patients and used nonparametric methods. Compared to the normative sample, the Inhibitedness, Health Concerns, and Emotionality scales had significantly higher raw scores. The Social Orientation, Frankness, and Extraversion scales had significantly lower raw scores. Health status was a medical factor that influenced the Somatic Complaints scale, patients who had lesions or comorbidities had significantly higher raw scores. Patients who had comorbidities in addition to IBD had considerably higher raw scores on the Excitability scale. Psychotherapeutic change interventions regarding life perception are required to tackle the description of subjective suffering related to physical inconveniences (Somatic Complaints scale), a strong orientation toward performance (Strain scale), mood swings, anxiety, and pessimism (Emotionality scale). Another intervention is reconsidering values and (re) prioritization, such as family, intimate relationships, friends, health, growth, development, balanced work, all of which can promote a feeling of well-being and balance.